THE ROLE OF HEALTH AWARENESS FOR PARTICIPATION IN SCREENING FOR BREAST CANCER (TRAKIA JOURNAL OF SCIENCES, 2025)
PURPOSE is to illustrate the need for increased health awareness of breast cancer (BC). METHODS: Documentary and sociological methods. A questionnaire survey was conducted among 811 women between March and April 2024. The questions concerned the presence of health habits, gynecological history and awareness of behavioral risk factors. RESULTS: 67% regularly participate in preventive care through clinical examination, and 12% have never had one; 76% have unhealthy habits related to coffee consumption, alcohol consumption, smoking, and insufficient sports activity; 84% declare a gynecological consultation in the last 3 years; 29% follow up their health in the private sector; 49% have had a regular clinical breast examination and 72% an ultrasound; 48% are not regular in having a mammogram; 42% trust the doctor’s opinion expressed in talks, TV programmes, advertisements; 41% the internet, specialist platforms and social networks, 59% prefer information in leaflets.   CONCLUSION: The lack of healthy habits and behaviors can be explained by imperfect knowledge of the benefits and systematic underestimation of the productivity of medical care. Increasing health literacy will make individuals rethink the positive and negative effects of specific behavior, which will affect their participation in screening programs.